2017
DOI: 10.1186/s12879-017-2930-7
|View full text |Cite
|
Sign up to set email alerts
|

The risk of nontuberculous mycobacterial infection in patients with Sjögren’s syndrome: a nationwide, population-based cohort study

Abstract: BackgroundNontuberculous mycobacterial (NTM) infection in immunocompromized patients is currently a growing health concern, and we aimed to examine the relative risk of NTM infection in patients with Sjögren’s syndrome (SS) compared with that in non-SS individuals.MethodsWe used the 2003–2012 Taiwanese National Health Insurance Research Database to identify 6554 incident SS cases during 2007–2012 and selected 98,310 non-SS controls matched (1:15) for age, gender, and the year of first SS diagnosis date after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The coexistence between NTM disease and chronic heart failure, GERD, other cancer, and rheumatoid arthritis has been reported previously [8,9,16]. Chao et al [23] reported an increased risk of NTM [24]. NTM-LD may be an underlying condition in patients with Sjögren syndrome because some patients with Sjögren syndrome have been reported to develop bronchiectasis [25,26], and pulmonary involvement in patients with Sjögren syndrome can be difficult to distinguish from NTM-LD using CT.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The coexistence between NTM disease and chronic heart failure, GERD, other cancer, and rheumatoid arthritis has been reported previously [8,9,16]. Chao et al [23] reported an increased risk of NTM [24]. NTM-LD may be an underlying condition in patients with Sjögren syndrome because some patients with Sjögren syndrome have been reported to develop bronchiectasis [25,26], and pulmonary involvement in patients with Sjögren syndrome can be difficult to distinguish from NTM-LD using CT.…”
Section: Discussionmentioning
confidence: 93%
“…The coexistence between NTM disease and chronic heart failure, GERD, other cancer, and rheumatoid arthritis has been reported previously [ 8 , 9 , 16 ]. Chao et al [ 23 ] reported an increased risk of NTM disease in patients with Sjögren syndrome based on an analysis of Taiwan’s National Health Insurance Research Database analysis. Pulmonary abnormalities have been described as an extra-glandular involvement of Sjögren syndrome [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent study among persons living in Taiwan and with Sjögren's syndrome, a systemic chronic inflammatory disorder characterized by lymphocytic infiltrates in the exocrine glands, those treated with immunosuppressants were 25 times more likely to have an incident NTM infection than those treated without immunosuppressants. 26…”
Section: Pntm Prevalence In High-risk Populationsmentioning
confidence: 99%
“…The coexistence between NTM disease and chronic heart failure, GERD, other cancer, and rheumatic arthritis has been reported previously [8,9,16]. Chao et al [28] reported an increased risk of NTM disease in patients with Sjögren syndrome based on an analysis of Taiwan's National Health Insurance Research Database analysis. Pulmonary abnormalities have been described as an extra-glandular involvement of Sjögren syndrome [29].…”
Section: Discussionmentioning
confidence: 72%